Comparative analysis of a portable smartphonebased electrocardiograph (DHeart®) versus standard 6leads electrocardiograph in the canine patient. (International Journal of Health, Animal Science and Food Safety, 2017)
D-Heart® is a portable, smartphone-based device, which streams tracing via Bluetooth, enabling multiple leads electrocardiograms (ECGs) acquisition, currently used in human cardiology (Maurizi et al. 2017).The aim was to determine the accuracy of DHeart® compared with the gold standard nonportable 6lead electrocardiograph in the evaluation of cardiac rhythm in dogs.Standard 6lead and DHeart® ECGs were acquired in conscious dogs. Concordance between methods was assessed by weighted k Cohen index, with its relative significance, taking as end point variable standard 6lead ECG group. Bland Altman method (95% confidence level) was applied for P, PR, QRS, T and QT. Since differences didn’t follow a normal distribution, a nonparametric approach was used to determine limits of agreement. P was significant when < 0.05 (Maurizi et al. 2017). Amplitude of waves was not considered because currently the software doesn’t allow voltage variation.115 dogs of different weights and breeds admitted to the Cardiology Service of DIMEVET were enrolled. Mean age was 7,5±4 years. Most were intact males (45%, n=51). The most represented breed was mongrel (27%, n=32).Weighted Cohen's kappa test demonstrated excellent concordance in the evaluation of the heart rhythm (0.989, p
Keywords: Electrocardiography; Dog; Heart; Rhythm; Arrhythmia